TRANSFER PRICING: DIRECTIONS OF THE IMPROVEMENTS OF THE TAX BASE FORMATION REGULATING - A. Ardashev (Вестник университета)
The directions of the development of the rules governing the process of formation of tax bases existing in the context of intra-group relations are considered. Regulation of prices formed in the process of intra-group operations, has passed several stages in its development. Nowadays, there are various approaches, which are often used in practice, as an alternative to each other. The problems associated with applying the arm’s length principle in practice are outlines in the article. The solution of these problems consist of the development of hybrid approaches that combine certain elements of the exist approaches and those used at present. Such a decision seems to be a temporary measure, since methods based on the arm’s length principle seems to be sucient, but with the assumption that the information required for their application will be available.